2021
DOI: 10.2147/dmso.s301747
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Visual Function Effects of Pan-Retinal Photocoagulation in Diabetic Retinopathy and Its Impact in Real Life

Abstract: Purpose: To address the long-term visual function after bilateral pan-retinal photocoagulation (PRP) and its impact in real life, namely on visual field (VF) legal criteria to drive. To determine potential predictors related to clinical factors and treatment strategies. Patients and Methods: Observational cross-sectional study. Eyes from diabetic patients diagnosed with diabetic retinopathy who underwent bilateral PRP, with or without macular treatments and with visual acuity legal criteria for non-professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…12 Austin Research Center for Retina, Austin, TX, USA. 13 Bristol Eye Hospital, Bristol, UK. 14 Retina Consultants of Texas, Houston, TX, USA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Austin Research Center for Retina, Austin, TX, USA. 13 Bristol Eye Hospital, Bristol, UK. 14 Retina Consultants of Texas, Houston, TX, USA.…”
Section: Discussionmentioning
confidence: 99%
“…The current gold-standard treatment for advanced DR, and in particular PDR, is a combination or individual use of panretinal photocoagulation and intravitreal anti-vascular endothelial growth factor (anti-VEGF) therapy [8,9]. However, many patients do not respond fully to these treatments [10][11][12][13][14]. Furthermore, panretinal photocoagulation can be associated with loss of visual field, decreased night vision and increased macular oedema, and there is a burden associated with receiving intravitreal treatment that can lead to non-compliance and, in turn, lower efficacy [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…However, monitoring the long-term visual rehabilitation outcomes is essential, as PRP can lead to visual field changes and potential visual function effects. A study found that the functional results achieved in patients undergoing bilateral PRP were compatible with an active life, allowing most patients to meet the legal criteria for driving, which is related to visual field requirements [ 50 ]. Another study demonstrated that despite achieving PDR stability, most patients lost clinically meaningful vision [ 48 ].…”
Section: Reviewmentioning
confidence: 99%
“…It treats retinal ischemia directly by ablation and allows for increased oxygen diffusion from the choroidal circulation [17] , [36] , [54] , [55] . Application of laser in a pan-retinal fashion may however cause reduction of night vision and/or reduction of the visual field as it reduces the amount of retina available for functional vision requirements [57] , [58] . These known co-morbidities of laser treatment highlight some of the potential benefits of anti-VEGF monotherapy for PDR.…”
Section: Diabetic Retinopathymentioning
confidence: 99%